2nd ASiD Innovation & Creativity Day (AiCD2019): Proceeding Book - Sapeli, Megat Mohd Izhar (Centre of Foundation Studies, 2020)
In line with the key purpose of tertiary education to generate holistic graduates who can compete globally and be ready to take on challenges, technological development plays a crucial role especially in the era of the Industrial Revolution 4.0 (IR 4.0). Academicians should be dynamic and adapt to various changes, being able to diversify teaching and learning methods via the culture of innovation, creating an immersive experience in the learning process for students. Hence, this event, ASID Innovation and Creativity Day (AICD) 2019 is aimed to provide a platform and opportunity for the academicians and students unleash their creative potential, skills and innovation. We are pleased to present the AICD2019 Proceeding Book as its published record.